Study on the Delineation of Small Layers and Depositional Micro-Phases in the Qing San Section of the Gaotaizi Formation in Qian'an Oilfield Block 130 - Yang Pengcheng; Zhang Qingguo; Li Zhixiang; Yang Shuyu (E3S Web of Conferences, 2023)
The fine isochronous comparison and fine portrayal of sedimentary micro-phases for the stratigraphy of Qian130 block in Qian'an oilfield is a critical problem that needs to be solved in the field nowadays. The target section of the study is the XII Sand Formation in Section III of the Upper Cretaceous Qingshankou Formation, and the oil-bearing formation is the Gaotaizi Oil Formation. Based on field outcrops, cores, logs and other data, a comparative stratigraphic framework of small stratigraphic levels was established and single well phases, continuous well profiles and planar sedimentary phases were studied for the deltaic foreland depositional system of the three sections of the Qingshankou Formation in the Qian'an Oilfield, guided by stratigraphic stratigraphy theory[1-2]. The analysis concludes that the regional structure is located in the northern part of the Changling Depression in the central depressional area of the southern part of the Songliao Basin, where faults are developed. The three sedimentary microphases of the Qingshankou Formation include six microphases: submerged divergent channel, estuarine dam, submerged divergent channel flank, submerged divergent interbay, distant sand dam, and matted sand. Combining the sedimentary micro-phase map of the small layer time unit with the oil formation sandstone thickness map, sand-to-ground ratio map and effective thickness map of the oil formation, the oil and water distribution in the study area is correctly understood to guide the next development of the Qian'an oil field[3-4].